DHAV-1 Inhibits Type I Interferon Signaling to Assist Viral Adaption by Increasing the Expression of SOCS3 - Xie, Jinyan; Wang, Mingshu; Cheng, Anchun; Zhao, Xin-Xin; Liu, Mafeng; Zhu, Dekang; Chen, Shun; Jia, Renyong; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; Liu, Yunya; et al. (Frontiers in Immunology, 2019)
Duck hepatitis A virus type 1 (DHAV-1) is one of the most lethal pathogens in the duck industry. The attenuated vaccine (the CH60 strain) is cultivated through serial passage in chicken embryos and is widely used for the prevention and control of the disease. However, the specific mechanism underlying its adaptation in chicken embryos has not been fully elucidated. In this study, we first infected chicken embryo fibroblasts (CEFs) with the DHAV-1 CH60 strain. The peak of viral proliferation occurred within 36-48 h post infection. The different DHAV-1 strains significantly induced the expression of IFNα, IFNγ, and Suppressor of cytokine signalling 3 (SOCS3) in CEFs, and we found that SOCS3 overexpression significantly promoted viral replication. Furthermore, SOCS3 overexpression significantly inhibited the expression of IFNα but promoted the expression of IFNγ. In addition, SOCS3 overexpression clearly decreased the mRNA levels of STAT1 and STAT3 in the Janus kinase (JAK)-STAT signalling pathway and inhibited the expression of the antiviral proteins MX1 and OASL. Immune-precipitation assays indicated that SOCS3 and IFNα do not physically interact. Subcellular localization of SOCS3 and IFNα revealed that SOCS3 was mainly located in the nucleus and cytoplasm, while IFNα was located only in the cytoplasm. Co-localization of these two proteins was not observed in the cytoplasm. In conclusion, the DHAV-1 CH60 strain may inhibit the expression of IFNα by increasing the SOCS3 protein and SOCS3 can in turn decrease STAT1 and STAT3 mRNA levels, thereby inhibiting the antiviral protein MX1 and ultimately promoting viral proliferation, indirectly assisting in viral adaptation in chicken embryos.